DECENTRALIZATION OF POLICY AND HANDLING OF DRUG ABUSE IN LABUHANBATU DISTRICT - Henky Dalimunte; Henry Aspan; Mhd. Azhali Siregar (International Journal of Synergy in Law, Criminal, and Justice, 2024)
Drug abuse is a serious problem in Indonesia, including in Labuhanbatu Regency, which has experienced a significant increase in drug abuse cases. Policy decentralization gives local governments the authority to address this issue according to local conditions, but often faces challenges such as limited resources, poor coordination, and limited institutional capacity. This study uses a qualitative approach with legislative and case study methods, is descriptive-analytical, and focuses on the analysis of legislation and policy implementation at the local level. Data were obtained from policy documents, official reports, and through documentation and observation techniques of legal products. The analysis was carried out using thematic analysis methods, categorizing the main themes from the results of documentation and observation to answer the formulation of the problem and achieve the objectives of the study. The results of the study indicate that the implementation of policy decentralization in Labuhanbatu Regency requires strengthening through the formation of comprehensive Regional Regulations (Perda), which include the preparation of an annual Regional Action Plan (RAD), the formation of an integrated cross-sector team, strengthening rehabilitation services, utilizing technology, and community participation in drug prevention and handling efforts. With a measured, structured, and participatory approach, it is hoped that the decentralization policy can be implemented effectively to optimize the handling of drug abuse in Labuhanbatu Regency.